2023
DOI: 10.3389/fphar.2023.1111462
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the cuproptosis-related gene DLD across cancers: A potential prognostic and immunotherapeutic target

Abstract: DLD is a key gene involved in “cuproptosis,” but its roles in tumor progression and immunity remain unclear. Exploring the potential mechanisms and biological roles of DLD may provide new insights for therapeutic strategies for tumors. In the present study, we analyzed the role of DLD in a variety of tumors by using several bioinformatic tools. The results showed that compared with normal tissues, tumor tissues representing multiple cancers showed significant differential expression of DLD. High DLD expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It was reported that the level of neutrophils in ltration was signi cantly increased in the group with high prognostic risk of LUSC (Ma, Wang et al 2023). In LUSC, neutrophil in ltration levels were also signi cantly positively correlated with other prognostic risk factors such as GLUT1 and DLD (Zhang, Dong et al 2022, Yang, Guo et al 2023). These ndings support our conclusions and indicated that the elevated expression of LPCAT1 may promote tumor in ltration of neutrophils, thereby inducing the recurrence and metastasis of LUSC.…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that the level of neutrophils in ltration was signi cantly increased in the group with high prognostic risk of LUSC (Ma, Wang et al 2023). In LUSC, neutrophil in ltration levels were also signi cantly positively correlated with other prognostic risk factors such as GLUT1 and DLD (Zhang, Dong et al 2022, Yang, Guo et al 2023). These ndings support our conclusions and indicated that the elevated expression of LPCAT1 may promote tumor in ltration of neutrophils, thereby inducing the recurrence and metastasis of LUSC.…”
Section: Discussionmentioning
confidence: 95%
“…DLD participates in the decarboxylation process of pyruvate, leading to the formation of acetyl coenzyme A within the tricarboxylic acid (TCA) cycle. During its redox activity, it has the potential to generate reactive oxygen species (ROS) ( 45 ). The overproduction of ROS hampers the effectiveness of other antioxidant defense mechanisms in NAFLD, leading to heightened oxidative harm ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…This platform facilitated the aggregation of gene data from numerous studies within a specific field, with publications sourced from the PubMed database. The protein–protein interaction network and functional enrichment analysis of the top studied genes were conducted through using Search Tool for the Retrieval of Interacting Genes (STRING) database, available at https://string-db.org/ 37 …”
Section: Methodsmentioning
confidence: 99%
“…The protein–protein interaction network and functional enrichment analysis of the top studied genes were conducted through using Search Tool for the Retrieval of Interacting Genes (STRING) database, available at https://string-db.org/ . 37 …”
Section: Methodsmentioning
confidence: 99%